Introduction to learning and behavior - Powell, Russell A. 1950-; Honey, P. Lynne; Symbaluk, Diane G. 1967- (Cengage Learning, 2017)
"Introduction to Learning and Behavior, 5th Edition provides you with a clear introduction to the basic principles of behavior presented in an accessible, engaging manner. Using examples derived from both animals and humans, the text vividly illustrates the relevance of behavioral principles to understanding and improving human behavior. The authors demonstrate the application of behavioral principles to such relevant issues as improving your study behavior, reducing procrastination, raising children, and managing relationships. To help you maximize your learning, the text is packed with innovative study and review tools to further your understanding of key concepts."--Provided by publisher.